Da dúvida à realização. O percurso atribulado e a missão de ser professor. - Rodrigo Dias da Costa (2020)
The professional internship is the final stage of the initial teacher training where all the experience takes place in the practical context (school) based on the various knowledge acquired in previous years. This report is part of the second cycle of the Master's Degree in Physical Education Teaching in Basic and Secondary Education at the Faculty of Sport of the University of Porto. In this document, I tried to report my whole adventure as a trainee teacher without escaping his setbacks and adversities. Here the whole process is lived in an intense and transparent way, from the first day at school to the melancholy at the end of this academic stage. I consider this report as a complex reflection on this passionate mission of being a teacher. Here are reflected my difficulties, the goals achieved, the relationship with the entire school community and, of course, all my thoughts on the various themes that accompanied me during the school year. I intend this report to be my real image and when you read it, glimpse my personality reflected in this incredible and difficult adventure as a teacher.